Success factors for stakeholder management for public-private partnerships infrastructure projects / Sakinah Khalidah Kaharuddin, Hamimah Adnan and Har Einur Azrin Baharuddin - Kaharuddin, Sakinah Khalidah; Adnan, Hamimah; Baharuddin, Har Einur Azrin (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Public-Private Partnership (PPP) has been identified as a procurement method that brings the public and private sectors together to facilitate the delivery of infrastructure projects and services. PPP manages complex projects and involves multiple stakeholders. Stakeholders in the PPP project need to be properly managed to achieve the project goals, minimising risk and accommodate stakeholder interest. Stakeholder management is about the relationship between organisation and its stakeholders. Poor management of stakeholder could lead to project failure. This paper aims to identify the success factors for stakeholder management in PPP infrastructure projects in Malaysia. A qualitative methodology which involved structured interviews with expert panels in PPP was conducted to validate the stages obtained from the primary and secondary data. The findings highlighted on the four (4) stakeholder management stages which involves stakeholder analysis, stakeholder engagement, stakeholder management action plan and stakeholder management monitoring. The needs for a having a clear understanding of the role of the project among stakeholders is crucial. Good stakeholder engagement is an essential part of project stakeholders' engagement. It also appears that the regulatory plan would be implication to contribute stakeholder management to achieve the success of PPP project. In addition, stakeholder must monitor the work on site in order to achieve project success. The success factors towards achieving a successful stakeholder management process have been identified. Improvement in these stages will lead towards better presentation and improvement of the success factors of stakeholder management process in PPP infrastructure projects in Malaysia.